Dynamic Structure of NREM Sleep - Halasz, Peter; Bodizs, Robert; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Dynamic Structure of NREM Sleep is a concise guide to Cyclic Alternating Pattern (CAP) phenomenology and slow wave homeostasis. It presents an original approach to a specialized aspect of sleep neuroscience in a concise and easy-to-read format. The authors are specialists in the field of sleep neuroscience and lend a new perspective to the benefits of slow wave activity during sleep. The main feature of this discussion is that slow wave activity increases as a function of previous wakefulness and it gradually decreases in the course of sleep. Alongside developing this idea, this book covers the entire range of sleep issues from basic structure to function in comprehensive detail. Dynamic Structure of NREM Sleep is valuable reading for neurologists, sleep neuroscientists and those with an interest in the field.
Introduction -- Development of the concept of wake- and sleep -promoting systems in the brainstem and hypothalamus -- Dynamic NREM sleep regulation models -- Recognition of spontaneous and evoked arousal- and sleep-like (antiarousal) phasic events -- The cyclic structure of sleep - Relationship between the macro-structural slopes of cycles and micro-structural dynamics -- Changing views of NREM sleep homeostatic regulation -- Homeostatic features of CAP system and the physiological mechanism of reactive slow wave activity -- Slow wave activity as substrate of homeostatic regulation -- Need of slow wave activity and cognitive functions -- Overview.
Keywords: Medicine; Neurosciences; Neurology; Medicine & Public Health; Neurology; Neurosciences